ANALISIS POSTFEMINIS PADA NOVEL NAMAKU MATAHARI KARYA REMY SYLADO - Arif Hidayat (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2012)
Abstract: This paper reveals novel Namaku Matahari (My Name Is The Sun) by Remy Sylado from the perspective of feminist literary criticism. This novel tells the story of a young woman named Margeretha Geertruida who is trying to find identity through identity as